Sacred and Secular Music in the Bible - Miliūnaitė, Miglė (Religija ir kultūra, 2017)
[full article and abstract in Lithuanian; abstract in English]This article deals with the issues arising within the relationship between sacred and secular music by analyzing musical properties found in the text of the Bible. Based on the opposition of the holy and the profane, which was posited by Mircea Eliade, the author tries to find the formation of this distinction by interpreting the characteristics of music in the Old Testament and its transformation in the New Testament. The aim of the article is to show that a measured rhythm and multivoicedness are features dominating in the secular sphere, while monophony can be seen as a fundamental feature of sacred music.
Keywords: sacred music; secular music; the Bible; Mircea Eliade